Sosialisasi Pendaftaran Sertifikasi Halal Terhadap Produk Makanan Kemasan Mikro, Kecil, dan Menengah (UMKM) di Desa Bukit Baling Kecamatan Sekernan Kabupaten Muaro Jambi - Faizah Bafadhal; Evalina Alissa; Diana Amir; Netty Netty; Meri Yarni (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
Halal Certification is a form of protection provided by the Halal Product Guarantee Organizing Agency (BPJPH) and the Indonesian Ulama Council (MUI) to provide security and comfort in consuming food for Muslim consumers regarding labels on food products. Halal certification for food products is very necessary, especially for Muslim consumers, in order to create consumer comfort in choosing the products they want to consume. The community service program in Bukit Baling Village, Sekernan District, Muaro Jambi Regency with the theme Socialization of Halal Certification Registration for food products for Micro, Small and Medium Enterprises (MSMEs) is to motivate the MSME community to register for halal certification for their food products, in order to provide comfort for Muslim consumers who consume these products. This Community Service Activity was carried out on August 15 2023, attended by The community and officials of Bukit Baling Village, Sekernan District Muaro Jambi Regency. This service is carried out using lecture, discussion and question and answer sessions.